2019
DOI: 10.1103/physreve.100.053101
|View full text |Cite
|
Sign up to set email alerts
|

Energy and enstrophy spectra and fluxes for the inertial-dissipation range of two-dimensional turbulence

Abstract: In this paper, using Pao's conjecture [Y.-H. Pao, Phys. Fluids 8, 1063(1965], we derive expressions for the spectra and fluxes of kinetic energy and enstrophy for two-dimensional (2D) forced turbulence that extend beyond the inertial range. In these expressions, the fluxes and the spectra contain additional factors of the exponential form. To validate these model predictions, we perform numerical simulations of 2D turbulence with external force applied at k = k f in the intermediate range. The numerical result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…The sum of the other triadic interactions leads to forward cascade, mainly local. The aforementioned non-local interactions leading to inverse energy cascade are also observed in two-dimensional hydrodynamic turbulence (Gupta et al 2019;Verma 2019).…”
Section: Non-local Energy Transfersmentioning
confidence: 91%
“…The sum of the other triadic interactions leads to forward cascade, mainly local. The aforementioned non-local interactions leading to inverse energy cascade are also observed in two-dimensional hydrodynamic turbulence (Gupta et al 2019;Verma 2019).…”
Section: Non-local Energy Transfersmentioning
confidence: 91%
“…For the stability analysis, we generate the stability matrix for S 1 and S 2 by linearizing Eqs. (27)(28)(29)(30) around S 1 , S 2 . This exercise yields a set of equations forũ 1 (k),ũ 1 (p), u 1 (q), andũ 1 (s) similar to Eqs.…”
Section: B Stability Analysis Of S 1 and Smentioning
confidence: 99%
“…The Kolmogorov flow is useful not only for analyzing transition to turbulence but also for studying the inverse cascade in two-dimensional turbulence [26][27][28] . Green 26 reported that for k > k f , kinetic energy spectrum, E(k) ∼ k −5 whereas for k < k f , E(k) ∼ k. Sommeria 17 studied the inverse cascade experimentally and reported that the exponent to be in the range of −4.5 to −4.9 for k > k f .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 A vortex is a type of phenomenon observed in 2D, and the parameters related to the strength of the vortex are often discussed in 2D observation. 18,19,22 However, the swirling character of 3D flow is somewhat more complicated than vortex flow because of the helical spiral component of the flow stream in 3D. The parameter to evaluate the helical flow structure is Helicity H.…”
Section: Parameters To Evaluate Vortical and Helical Flowmentioning
confidence: 99%